Sleep quality and quality of life in patients with moderate to very severe chronic obstructive pulmonary disease. (4th December 2017) - Akinci, Buket; Aslan, Gökşen Kuran; Kiyan, Esen
Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is highly associated with obstructive sleep apnea (OSA). Poor sleep quality is found to be related with decreased quality of life (QoL) in patients with COPD but no study assessed this relationship on the basis of nocturnal sleep parameters. Objectives: The aim of this study is to explore the relationships between sleep quality, daytime sleepiness and QoL in patients suffering from moderate to very severe COPD with and without sleep apnea assessed objectively and to compare sleep quality, QoL and daytime sleepiness in patients suffering from COPD with and without sleep apnea. Methods: Fifty‐one patients with stable moderate to very severe COPD (mean age, 59.8 ± 8.1 years) included in the study. The parameters of polygraphic sleep studies (Stardust II, Philips‐Respironics) were noted. Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), The Modified Medical Research Council Dyspnea and SF‐36 Health Quality Survey were performed. Results: The rate of OSA was 74.5% (Apnea‐Hypopnea Index, >5). out of all the patients, 94% had poor sleep quality (PSQI, >5). Negative correlations were found between PSQI and physical role, social function and mental health of SF‐36 subgroups ( P  < .05). There was no correlation between PSQI, ESS, SF‐36, dyspnea and polygraphic parameters ( P  > .05). In the comparison of patients with or without OSA, the vitality of SF‐36 subgroup was found lower in patients with OSA ( P  < .05). Conclusions: In conclusion, irrespective of OSA, patients with COPD are suffering from poor sleep quality and poor sleep quality negatively affects the QoL. Also, COPD and OSA association causes worsened vitality in the terms of health‐related QoL.